A new model for the dynamic analysis of heavy-haul locomotives with cylindrical pin coupler and buffer systems. Issue 10 (3rd October 2022) - Zhang, Zhichao; Chu, Gaofeng; Zu, Honglin; Zhang, Yizhe; Li, Gu
Abstract : This paper proposes a new model of the cylindrical pin coupler and buffer system and then a more accurate train dynamic model to investigate the heavy-haul locomotive dynamic performance and running safety. In this new model, the buffer bias pressure characteristic is simulated accurately by discretising the real polymer buffer linearly into seven impedance force elements of the same non-linear hysteresis characteristic but different weighting coefficient, and the shear effect between them is considered by setting an additional deflection stiffness. Then a heavy-haul train dynamic model consisting of one locomotive, two wagons and three sets of coupler and buffer systems is established and validated by comparing its calculation results with test data. The simulations are carried out to investigate the influences of curve radius, locomotive and coupler structural parameters on the locomotive dynamic responses and running safety. Results indicate that the coupler rotation angles and locomotive running safety index increase gradually with the decrease in curve radius. And the elastic stiffness and free clearance of locomotive secondary lateral stops also have great influences, weakening the lateral stop constraint would cause the increase of the coupler rotation angles but the decrease of the wheel–rail forces and running safety index.